Lipid Emulsion, More Than Reversing Bupivacaine Cardiotoxicity: Potential Organ Protection - Negar Motayagheni; Sheshanna Phan; Ala Nozari; Anthony Atala (Journal of Pharmacy & Pharmaceutical Sciences, 2018)
Efforts to develop a treatment for bupivacaine cardiotoxicity led to the discovery that Intralipid, a popular brand of intravenous lipid emulsion, could be used not only as an effective treatment for anesthetic-induced cardiac arrest, but also as a means of reversing many other toxicities. Contradictory data exist regarding the mechanism of action of lipid emulsion, a combination of fatty acids traditionally used in parenteral nutrition. Some researchers attribute the effects to lipophilicity and the individual characteristics of the lipids, while other data demonstrate a direct empowering mechanism through cellular upstream and downstream pathways. Understanding the underlying mechanism of action of this safe source of calories may assist in the development of novel organ protective agents. In this review, some of the direct cardiac effects of lipid emulsion are briefly discussed.